(untitled) - Salvatore, R.A.; 1959- (Wizards of the Coast, 2008)
The Arcane Brotherhood has long held the city of Luskan in their power, but when corruption eats away at their ranks, Captain Deudermont comes to the rescue of a city that has become a safe haven for the Sword Coast's most dangerous pirates. But rescuing a city from itself may not be as easy as Deudermont thinks, and when Drizzt can't talk him out of it, he'll be forced to help.
"Forgotten realms."
"A Dungeons & Dragons book"--dust jacket.
Keywords: Imaginary wars and battles; Fiction; Fiction; Forgotten realms (Imaginary place); Dwarfs; Fiction; Drizzt Do'Urden (Fictitious character); Fiction; Fantasy fiction